Free-form External Design using BIM and Development of Grasshopper Model - Kim, Sangchul; Eom, Shinjo (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, the number of free-form buildings using BIM(building information modeling) technology is increasing, but it is difficult to design and manufacture non-linear external panels of free-form buildings. Methods/Statistical analysis: In this study, the research team will develop the technology for easily creating non-linear surface panels using BIM, develop a scalable 3D external design process based on grasshopper module, and validate the engineering feasibility through simulation. The methods for making grasshopper modules are based on optimization techniques, algorithms, analysis of existing cladding panel technology, and analysis of existing fabrication methods Findings: In order to develop grasshopper model, the first step is generating the optimization algorithm. To find the algorithm, we considered three alternatives, 1) the method of extracting and utilizing the coordinate point in the initial design of Grasshopper and applying the minimum interval to the concept mass of Revit while keeping the original plan, 2) Designing the design through connection of the minimum interval (coordinate point) of the interval on the U. V grid in the concept mass stage using Revit in the early stage, and 3) It is a plan to utilize Dynamo. Then, based on three options, 1) and 2) were combined to develop the technology. And the validation of proposed technology was performed between existing fabrication methods and the proposed methods by 4 major categories.- accuracy, waste reduction, optimization, and congruity. In all aspects, the proposed method was exceeded over the level of existing technique. Improvements/Applications: The research team developed a design process that can produce exterior panels of free-form buildings through optimization, algorithm, and Grasshopper. The results are applicable to all areas of construction. Â Â